Teacher Identity in Transition: A Growth Mindset Perspective from Pre-Service Mathematics Teaching Practice - Arviolita, Dea; Maharini, Dina; Evrihatin, Dita Susi; Herawati, Any; Trisniwati, Retno; Faradiba, Surya Sari (Jurnal Likhitaprajna, 2026)
This study explores how teacher identity is constructed and enacted through a growth mindset perspective in a pre-service mathematics teacher. Recognizing that teacher identity is dynamic and shaped through practice, this research aims to investigating how growth-oriented beliefs are reflected in instructional discourse and classroom interaction. A qualitative case study design was employed, focusing on a pre-service teacher conducting a teaching practicum in a State Senior High School 3 Malang. Data were collected through classroom teaching transcript derived from a recorded lesson on compound interest and analyzed using discourse analysis to identify patterns related to growth mindset and teacher identity. The findings reveal that the teacher demonstrates an emerging growth mindset through effort encouragement, valuing process, normalizing mistakes, and student agency, and challenge orientation. These practices position the teacher as a motivator and facilitator who supports student engagement and confidence. However, the teacher also frequently adopts authoritative and evaluative roles, particularly when emphasizing procedural accuracy and providing direct instruction. This indicates a tension fostering student-centered learning and ensuring correct mathematical understanding. Overall, the study highlights that teacher identity is constructed as a hybrid and transitional process, where growth mindset beliefs coexist with traditional instructional practices. The findings suggest that developing a growth mindset in teaching requires alignment between beliefs and classroom practices. Therefore, teacher professional education programs should support reflective practice to help pre-service teachers integrate growth-oriented principles more consistently in their teaching.